2008
DOI: 10.1074/jbc.m709695200
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Levels of Oncogenic Protein Kinase Pim-1 Induce the p53 Pathway in Cultured Cells and Correlate with Increased Mdm2 in Mantle Cell Lymphoma

Abstract: Mutation of the p53 gene is a common event during tumor pathogenesis. Other mechanisms, such as mdm2 amplification, provide alternative routes through which dysfunction of the p53 pathway is promoted. Here, we address the hypothesis that elevated expression of pim oncogenes might suppress p53 by regulating Mdm2. At a physiological level, we show that endogenous Pim-1 and Pim-2 interact with endogenous Mdm2. Additionally, the Pim kinases phosphorylate Mdm2 in vitro and in cultured cells at Ser 166 and Ser 186 ,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
1
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(72 citation statements)
references
References 55 publications
(113 reference statements)
4
64
1
3
Order By: Relevance
“…We further showed that this decrease in miR-1 expression is associated with an increase in oncogenic MET, Pim-1, FoxP1, and HDAC4. Pim-1 is a Ser/Thr kinase overexpressed in various human cancers and plays a causal role in lymphoma and leukemogenesis (50,51). Our study shows that it is also up-regulated in the majority of human primary lung tumors and cancer cell lines.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…We further showed that this decrease in miR-1 expression is associated with an increase in oncogenic MET, Pim-1, FoxP1, and HDAC4. Pim-1 is a Ser/Thr kinase overexpressed in various human cancers and plays a causal role in lymphoma and leukemogenesis (50,51). Our study shows that it is also up-regulated in the majority of human primary lung tumors and cancer cell lines.…”
Section: Discussionmentioning
confidence: 57%
“…Oncogenic Ser/Thr Kinase Pim-1, a Target of miR-1, Is Significantly Up-regulated in Lung CancerPim-1, a Ser/Thr kinase, induces tumorigenesis by promoting cell cycle progression and inhibiting apoptosis (50,51). Since its 3Ј-UTR harbors one miR-1 cognate site (Fig.…”
Section: Foxp1 and Hdac4 Targets Of Mir-1 Are Also Differentially Rmentioning
confidence: 99%
“…PIM1 associated with and phosphorylated Mdm2 at Ser166 and Ser186 leading to stabilization of both proteins. 66 More work is needed to validate the impact of PIM-mediated p53 regulation for induction and/or maintenance of malignant transformation.…”
Section: Pim2mentioning
confidence: 99%
“…12 In addition, elevated Pim-1 expression in MCL has been reported to induce the p53 pathway and correlate with increased expression of MDM2. 13 Furthermore, Pim-1 expression is known to be highly associated with poor outcome in MCL patients. 7 These observations suggest that Pim kinases could be potential therapeutic targets in MCL.…”
Section: Introductionmentioning
confidence: 99%